Monitoring socioeconomic inequity in maternal health indicators in Egypt: 1995-2005 - Khadr Zeinab (BMC, 2009)
Abstract Background Egypt's longstanding commitment to safe motherhood and maternal health has paid off in substantial declines in maternal mortality ratio and significant improvement in the levels of many maternal health indicators. The current study aims to monitor trends of maternal health indicators and their socioeconomic inequities among Egyptian women over ten-year period (1995-2005). It poses the question "to what extent have the recent maternal health improvements been shared among the various socioeconomic categories of women?" Methods The current paper uses data on maternal health available in three consecutive Demographic and Health Surveys (1995-2000-2005). Concentration index is used to assess the levels of health inequity over the ten year period. Results Although previous efforts in maternal health have contributed to substantial improvements in the general levels of maternal health indicators, these improvements were not enjoyed equally by women in various social groups. Indicators that have long been the focus of health policy such as fertility and contraceptive use showed some declines in disparities but they are far behind from achieving equity. Other indicators which relate to unmet need, prenatal care, delivery, postnatal care still loaded with high levels of inequity and call for more comprehensive policy interventions.